Performance and methane emissions of grazing Nellore bulls supplemented with crude glycerin - Vito, E. San [UNESP] (2016)
Supplementation of grass-fed cattle with low-cost feeding alternatives may be an attractive way to improve efficiency of cattle production. We hypothesized that inclusion of crude glycerin (CG) in supplements provided to grass-fed cattle could improve feed conversion without negative effects on growth performance while reducing methane emissions. Our hypothesis was tested using Nellore bulls grazing tropical pasture (n = 50; initial BW of 427 +/- 19.41 kg; age of 17 +/- 2 mo) supplemented with increasing concentrations (0, 70, 140, 210, and 280 g/kg DM basis of supplement) of CG and corn gluten replacing corn grain. A second experiment was conducted using 10 ruminally cannulated Nellore steers (490.1 +/- 47.8 kg BW; age of 25 mo) to assess the impact of different concentrations of glycerin in the supplement on ruminal VFA concentration. Inclusion of CG did not affect total DMI (P = 0.53), DMI of forage (P = 0.41), supplement DMI (P = 0.47), organic matter intake (P = 0.50), crude protein intake (P = 0.24), NDF intake (P = 0.49), GE intake (P = 0.50), NDF digestibility (P = 0.17), final BW (P = 0.17), LM area (P = 0.50), rib fat thickness (P = 0.87), or carcass gain (P = 0.13). The inclusion of CG in the supplement linearly increased (P < 0.001) the molar proportion of propionate, butyrate, and valerate; linearly decreased acetate (P = 0.001); and did not affect the molar proportion of isovalerate (P = 0.31) and isobutyrate (P = 0.63), thereby reducing the acetate to propionate ratio (P < 0.001). The increase of CG supplementation of young bulls in pasture had a quadratic effect on BW gain (P = 0.002), with lower BW gain with 140 g/kg DM of CG in the supplement and tended (P = 0.06) to improve G:F. Inclusion of CG did not affect ruminal CH4 emission expressed in kilograms per year (P = 0.74), grams per kilogram of DMI (P = 0.69), and grams per kilogram of carcass gain (P = 0.48). Crude glycerin supplementation was not effective as a strategy to reduce CH4 emission in grass-fed cattle. However, CG can be effectively used as a partial energy source in supplement of grazing cattle, promoting an improvement in feed efficiency.